APLIKASI PENGADUAN MASYARAKAT BERBASIS MOBILE WEB DI KECAMATAN TARUTUNG - Sofya C. Sitompul; Jamaluddin Jamaluddin; Roni Jhonson Simamora; Resianta Perangin-angin (Universitas Methodist Indonesia, 2019)
Public complaints are an important element in government agencies because complaints aim to improve the shortcomings of activities carried out by the government. Complaints from the Tarutung Subdistrict community have not been fully maximized regarding administrative activities in the sub-district including the schedule for distributing Raskin, taking family card files, ID cards, and others. Based on the background of the above thoughts can be identified as a problem that is how to design an application for public complaints services and information that can be felt directly by the community without having to spend much time on the complaints process. The purpose of this study is to build a mobile web-based application that can be accessed through a web browser. This application is built with the PHP programming language and uses the MySQL database as a database server. The results of this research are complaints applications that provide convenience in terms of online public complaints.